Copeptin Levels in Cerebral Infarction, Intracranial Hemorrhage and Subarachnoid Hemorrhage - Aksu, Feyza; Gurger, Mehtap; Yilmaz, Mustafa; Atescelik, Metin; Yildiz, Mustafa; Ilhan, Nevin; Goktekin, Mehmet C. (Clin Lab Publ, 2016)
Background: To determine copeptin levels in patients with suspected intracranial events and to determine whether copeptin levels could be used in the discrimination of cerebral infarction, intracranial hemorrhage, and subarachnoid hemorrhage in the emergency room. Methods: Blood samples were obtained from the patients prior to imaging to determine the levels of copeptin. Patients were divided into diagnostic groups after the imaging. One hundred and seventy-six participants, who were enrolled in the study, were as follows: 50 cerebral infarction (CI) patients (M/F: 24/26), 47 intracranial hemorrhage (ICH) patients (M/F: 27/20), 29 subarachnoid hemorrhage (SAH) patients (M/F: 17/12) and 50 healthy controls. Differences and correlations between groups were analyzed. Results: Plasma levels of copeptin in patients with CI, ICH, and SAH were 5.49 ng/dL (IQR 4.73 to 6.96), 4.50 ng/dL (IQR 3.04 to 9.77), and 5.90 ng/dL (IQR 3.11 to 13.26), respectively. It was found to be 2.0 ng/dL (IQR 1.57 to 2.5) in healthy volunteers. There was no significant correlation between copeptin levels and Intracerebral Hemorrhage Score (ICHS) (r = 0.231, p = 0.118). However, significant positive correlation was found between copeptin levels with the National Institutes of Health Stroke Scale (NIHSS) (r = 0.365, p = 0.009) and the BotterelHunt and Hess Scale (BHHS) (r = 0.590, p = 0.001). The copeptin levels of 41 (32.5%) patients who died were found to be significantly higher than those 85 (67.5%) patients who were discharged (p < 0.001). Conclusions: Copeptin levels in patients with CI, ICH, and SAH are significantly higher than healthy volunteers, but the plasma level of copeptin is not decisive in the discrimination of CI, ICH, and SAH.
Keywords: cerebral infarction; copeptin; intracerebral hemorrhage; subarachnoid hemorrhage